Bakteriella polysackarider - enzymatisk syntes och jakt på nya nedbrytande enzymer - Bergentall, Martina; Chau, Christina; Engström, Enya; Johansson, Sofia; Lövgren, Sandra; Nordanger, Emma (My University, 2019)
A common problem in society today is tooth-related diseases caused by dental plaque. Dental plaque is a microbial biofilm which works like a protecting shield for organisms to live within, and consists of mostly water and polysaccharides. Dental plaque can eventually lead to diseases such as caries or tooth decay, hence treating dental plaque at an early stage is of importance. Despite preventional methods in use today, dental plaque is still a widespread global problem suggesting that these methods are insufficient. There are a limited number of enzymes known today which can break down mutan or alternan, which are two polysaccharides that can be found in the dental plaque matrix. This project aimed to isolate and categorise enzymes from microorganisms with the ability to break down mutan and alternan. A long-term goal with finding new enzymes able to break down the polysaccharides is to incorporate these enzymes in dental hygiene products. Since mutan and alternan are not commercially available they were produced from the enzymes GtfJ and GtfL, and then purified by centrifugation and filtration. To confirm the purity, the polysaccharides were tested by reducing sugar analysis and thereafter freeze-dried before use. The polysaccharides were then used as a carbon source in cultivation plates and in liquid media when cultivating microorganisms. Field studies were carried out for collection of samples in two green belts around the Gothenburg area. The sampling included water and soil samples from different biotopes, which were introduced to cultivation plates made up of agar and alternan or mutan. A cultivation plate only containing agar was used as control. Growth was studied for a couple of weeks, and some colonies which showed growth with a clearing zone were restreaked on additional cultivation plates. Thereafter, samples were inoculated into liquid media for faster growth and to generate a sufficient amount of DNA for sequencing. Samples which showed growth after inoculation, and had a clearing zone when restreaked, were analysed by 16S and ITS sequencing. Results from the sequencing showed the possible presence of a known fungal species, Brettanomyces bruxellensis, and also the probable presence of five fungal and bacterial species belonging to the genera Cladosporium and Paenibacillus. Out of the six species discovered, five of them were able to break down mutan and one of them was able to break down alternan. Due to lack of time the purpose of isolating and characterising enzymes from said microorganisms could not be achieved, and hence it is a possible subject for further studies. These studies may involve enzyme efficiency and function in vivo, along with comparisons between several di erent enzymes in order to obtain optimal enzyme characteristics.
Keywords: Mikrobiologi; Botanik; Odontologi; Livsvetenskaper; Microbiology; Botany; Dentistry; Life Science